تعزيز حقوق الملكية الفكرية في تقنيات الحلال لنقلها كمعرفة فنية = Strengthening Intellectual property rights (IPR) in Halal techniques to transfer it as KNOW-HOW - Laeba, Muhammad; Ahmed, Ahmed Salem (Journal of Halal Industry & Services (JHIS), 2018)
he study aim is the preserving of halal independence contents and investing it in the best investment. In the researcher's view, this can only be by the achieved through a legal framework that protect these continents and ensures the application integrity of it which led the researcher to make approach between the halal techniques and intellectual property rights principally trademarks, Geographical indications, trade data, know -how, patents, as well as traditional knowledge that recently incorporated within into (IPR), which has shown by Analytical and comparative methodology; the halal techniques has mated with the terms of those rights, And allows to invest it as an independent as a know -how that has its own specificity instead of continues the attempts that following to adopt the halal continents to meet the prevailing technical and legal systems related to the products. In the end by analyzing the legal mechanisms of technology transfer the researcher has reached that the joint projects are the most proper means to ensure the halal values and principles in the halal industry and offer halal products to the Muslim consumers and opens new horizo ns for Investment-linked directly with the labor market